Interactions of prismatic dislocation loops with free surfaces in thin foils of body-centered cubic iron. (15th October 2015) - Fikar, Jan; Gröger, Roman
Graphical abstract: Abstract: We employ molecular statics simulations to investigate the interactions of circular and hexagonal 1 / 2 〈 1 1 1 〉 prismatic loops in body-centered cubic iron with two parallel { 1 1 1 } free surfaces of a free-standing foil. If the presence of two surfaces is taken into account, these results agree well with the isotropic elastic solutions of Bastecka (1964) for circular loops and of Groves and Bacon (1970) for square loops with the Burgers vector of the loop perpendicular to the surface. By varying the size and shape of the loop, we identify the critical depth at which the image stresses overcome the internal lattice friction and thus drive the loop towards the surface. We investigate how this depth and the corresponding critical stress on the dislocation depend on the shape and size of the loop and outline how these results can be used to correct transmission electron microscope (TEM) measurements of the densities of prismatic dislocation loops in thin foils. For example, for the loops of 5 nm in diameter in a 50 nm thick foil, the loop density corrected for the existence of denuded zones adjacent to the surfaces of the foil is shown to be nearly 49% higher than that obtained by direct TEM measurements.